Numerical solution of Countercurrent Imbibition in Inclined Homogeneous Porous Medium by using Polynomial based Differential Quadrature Method - Amit K Parikh, Jishan K Shaikh (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In this research paper, we have studied mathematical exemplary of countercurrent imbibition phenomenon arising in slanted oil structured homogeneous porous medium. The governing equation is one dimensional nonlinear partial differential equation. The Polynomial based differential quadrature method used to obtain numerical solution of governing equation with suitable initial and boundary conditions. We used uniform and Chebyshev Gauss Lobatto grid points for obtaining numerical solution. We compared result obtained by Chebyshev and uniform grid points. We used MATLAB coding for Numerical and Graphical representation.